The Influence of Organizational Culture and Work Discipline on Employee Performance at PT. First Logistics Service Central Semarang Branch - Irma Sari Octaviani; Lidya Pricilla (Indonesian Development of Economics and Administration Journal, 2023)
The purpose of this study is to analyze the influence of organizational culture and work discipline on the performance of employees at PT. First, Logistics Service Central Semarang Branch. This study applies Associative methods, with descriptive and causal as the type of research, as well as multiple linear regression analysis. Then using saturated samples as a sampling technique, with a total of 60 respondents. Based on descriptive analysis, it proves that organizational culture, work discipline and employee performance fall into the good category. Simultaneously, organizational culture and work discipline have a significant influence on employee performance. The magnitude of the influence of organizational culture, work discipline, on employee performance is 30% and the influence of other variables that are not studied is 70%. While organizational culture has not been able to partially influence employee performance, only work discipline has been able to partially affect employee performance.